(NsWQZX SEJSMI^NOSTI zEMLI S SOLNE^NOJ AKTIWNOSTX@ I ATMOSFERNYMI PROCESSAMI (B/s - (NsYTINSKIJ(B, (NaLEKSANDR dMITRIEWI^s; (NtRO[I^EW(B, (No(B.(Na(B.s; (NkOROTKEWI^(B, (Ne(B.(Ns(B.s ((Nl(B. :s (NgIDROMETEOIZDAT(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 93-98 (132 (NNAZW(B.)s
Keywords: (NaTMOSFERAs; (NwLIQNIE SOLNE^NOJ AKTIWNOSTIs; (NsEJSMI^NOSTXs; (NcIRKULQCIQs